BACTERIOLOGICAL ANALYSIS OF POST MONSOON WATER SAMPLES FROM SELECTED AREAS OF RANCHI (JHARKHAND) - SOMA ROY; SUDIPTO ROY; SUNITA DUTTA; ABHIJIT DUTTA (The Bioscan, 2011)
The present study presents a regional picture of water contamination. It lays emphasis on access of poor quality water by the people from open wells due to absence of proper infrastructure of ground water management. Presence of coliforms was detected in 39 water samples revealing the presence of coliform in 40.62% of the samples. Out of 5 well water samples tested for specific pathogens the species isolated were Aeromonas hydrophila, Psedomonas putrefaciens, Salmonella paratyphi B, E.coli, Vibrio NAG, Streptococcus faecalis, Shigella.